ICAM-1 and CRP as biomarkers of 3-month outcome in acute ischaemic stroke - Gulnora Sattarovna Rakhimbaeva; Kutlibika Bakhtiyor kizi Abdurakhmonova (BMJ Neurology Open)
Background It is clear that, inflammation deteriorates cerebral injury during the acute phase of stroke. While this process is going on, intercellular adhesion molecule-1 (ICAM-1) has a crucial role to play in mediating migration of immune cells into the damaged area. Furthermore, C reactive protein (CRP) is an essential inflammatory molecule in human organism. This research aims to investigate the association between ICAM-1, highly sensitive CRP(hs-CRP) and the prognosis of acute ischaemic stroke (AIS).Methods 118 patients with AIS who were treated at Tashkent Medical Academy were participants in this research project. Blood samples were collected from patients on an empty stomach within 24 hours of admission. Modified Rankin Scale (mRS) was used in order to assess the functional prognosis in 3 months following the case of stroke in patients. The inadequate prognosis is described as mRS≥3. Each biomarker’s potential to predict has also been evaluated with receiver operating characteristic analysis.ResultsICAM-1 was identified to be an independent predictor of 3-month outcome (OR 1.05, 95 % CI 0.848 to 1.625; p=0.02) (area under the curve (AUC)=0.82 %). Independent associations with functional outcome were also found to be true for hs-CRP (OR 1.22, 95 % CI 0.78 to 1.86; p=0.03) (AUC=0.74 %).ConclusionsThe outcomes of a 3-month study carried out on patients with AIS showed ICAM-1 and hs-CRP to be independent predictors.